Applying Virtualization and System Management in a Cluster to Implement an Automated Emulation Testbed for Grid Applications - Calheiros, Rodrigo N.; Storch, Mauro; Alexandre, Everton; De Rose, César A. F.; Breda, Marcus (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2008: Anais do XX International Symposium on Computer Architecture and High Performance Computing, 2008)
Although grid systems have evolved in such a way that they are largely used both in industry and academy, techniques to test and evaluate them, such as simulation and emulation, have limitations on both their applicability and their reliability. We are investigating the utilization of paravirtualization techniques merged with systems management tools to build an automated emulation framework for grid experiments. This framework accesses standard network resources to manage communication among virtual nodes, allowing virtual machines to behave like a real grid environment. The development of this framework involves the mapping of virtual machines to physical hosts, automatic deployment and management of virtual machines, automatic configuration of virtual network and experiment control. In this paper, we address these issues and present results demonstrating the feasibility and advantages of our approach.